2013
DOI: 10.1371/journal.pone.0081267
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Population Structure and Analytical Models in Genome-Wide Association Studies of Complex Traits in Forest Trees: A Case Study in Eucalyptus globulus

Abstract: The promise of association genetics to identify genes or genomic regions controlling complex traits has generated a flurry of interest. Such phenotype-genotype associations could be useful to accelerate tree breeding cycles, increase precision and selection intensity for late expressing, low heritability traits. However, the prospects of association genetics in highly heterozygous undomesticated forest trees can be severely impacted by the presence of cryptic population and pedigree structure. To investigate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 87 publications
4
56
0
1
Order By: Relevance
“…This consideration of relatedness considerably reduced p -value inflation, for both traits. Similar results were reported for wood quality and growth traits in Eucalyptus globulus [70, 71] and for wood property traits in Cryptomeria japonica [72]. Only seven of the 2,498 SNPs, from six different loci, were found to be significantly associated with the traits considered (p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…This consideration of relatedness considerably reduced p -value inflation, for both traits. Similar results were reported for wood quality and growth traits in Eucalyptus globulus [70, 71] and for wood property traits in Cryptomeria japonica [72]. Only seven of the 2,498 SNPs, from six different loci, were found to be significantly associated with the traits considered (p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Although less genetic variation is in principle available in such structured populations, the associations detected in genetically improved material should be considerably more relevant to further breeding, as their effect would be relevant in an already elite background. Following an equivalent rationale, three studies have reported GWAS for growth and wood quality traits in breeding populations of Eucalyptus (Cappa et al ., ; Müller et al ., ; Resende et al ., ). Interestingly, the results were on par with those described earlier in natural populations, in which few associations explaining small fractions of the genetic variation were detected.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, however, hybridization‐based DArT arrays for eucalypts have supplied on average 3000 informative markers across species, increasing by an order of magnitude the ability to query polymorphisms across the genome (Sansaloni et al ., ). This has inaugurated genome‐wide mapping (Hudson et al ., ; Petroli et al ., ), QTL detection (Freeman et al ., ), association genetics (Cappa et al ., ) and genomic selection in eucalypts (Resende et al ., ). Nevertheless, the dominant behavior of DArT markers, together with limitations in expanding their number and distributing them equally across the genome, became concerns when considering large‐scale, fast turnaround genotyping for operational molecular breeding.…”
Section: Introductionmentioning
confidence: 99%